Coronavirus Diseases -19: an overview in education, agriculture, and communication perspectives - Ikawati Karim; Indah Nur Aini; M. Fikri Akbar (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
As it emerged at the end of December 2020 in Wuhan, China, Coronavirus has now spread to many countries, which affected several sectors of human life. This paper aims to describe the impact of covid-19 on education, agriculture, and communication in Indonesia. In education, COVID-19 impacted the teaching methods. Teachers utilized e-learning during the COVID-19 pandemic, such as Schoology, Edmodo, Google Classroom, Facebook, WhatsApp, and Zoom. In agriculture, coronavirus impacted downstream and upstream agriculture. As the main food producer, farmers should be protected from the dangers of the coronavirus to maintain food security. All people need to consume food based on agricultural products. In communication, coronavirus makes society change in the use of communication media. New media is more interactive and creates a new understanding of interpersonal communication.